If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3y + -12 = 4y + 88 Reorder the terms: -12 + 3y = 4y + 88 Reorder the terms: -12 + 3y = 88 + 4y Solving -12 + 3y = 88 + 4y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-4y' to each side of the equation. -12 + 3y + -4y = 88 + 4y + -4y Combine like terms: 3y + -4y = -1y -12 + -1y = 88 + 4y + -4y Combine like terms: 4y + -4y = 0 -12 + -1y = 88 + 0 -12 + -1y = 88 Add '12' to each side of the equation. -12 + 12 + -1y = 88 + 12 Combine like terms: -12 + 12 = 0 0 + -1y = 88 + 12 -1y = 88 + 12 Combine like terms: 88 + 12 = 100 -1y = 100 Divide each side by '-1'. y = -100 Simplifying y = -100
| C=50(215)+40 | | 1.5=50n+40 | | 2=50n+40 | | T=L(4+RS) | | 5(x-3)+4=2(x-4) | | 12x^2+17x-7=0 | | 5x+10=2(2x+5) | | (2a/3)+(7a/9)+2=0 | | 4y-20= | | -3kx^2+4x^2+26x-17=0 | | 11=x-4 | | 4a+13-a+7=7a+10+2-a | | 3x^2+5x-50=0 | | 11x=90-7x | | 12z/3=z-6 | | x-3/5=-1/2 | | 5y-3(y-2)+4= | | 55=(x+25) | | 5x+12=7x-8 | | 20+5x=4(x-3) | | 4x+10=100 | | 9y-47=y+73 | | 105+(3x-18)=180 | | 0=x^2+12x-6 | | -5(2+3)+3z= | | 5(y+4)=6(y-4) | | x^2+X^2=1 | | 5x+2x=2x-10 | | y^2+11y=12 | | 3y+30=-y+14 | | 3y+30=-y+13 | | 6m+2m+3=11 |